Abnormal aortic arch shape and vortical flow patterns are associated with descending aortic dilatation in patients with hypoplastic left heart syndrome. (15th January 2021) - Voges, Inga; Scheewe, Jens; Attmann, Tim; Uebing, Anselm; Oechtering, Thekla; Gabbert, Dominik
Abstract : Introduction: The descending aorta (DAo) in patients with hypoplastic left heart syndrome (HLHS) after Norwood procedure is frequenty enlarged and exhibits increased stiffness. Such findings of previous studies still remain unexplained given the fact that the DAo is not involved in the Norwood operation. Methods: We studied five HLHS patients with DAo dilatation (aged: 2.9–15.1 years (y), median 9.0 y), four HLHS patients without DAo dilatation (aged: 3.5–9.7 years, median 6.45 y) and 7 healthy controls (aged 6.3–41.6 y, median 26.0 y) using cardiovascular magnetic resonance imaging with acquisition of cine images, contrast-enhanced angiograms and 4D flow. 4D flow data were analyzed based on in-house developed analysis software to quantify vortical flow patterns in terms of vorticity. Results: All patients with DAo dilatation presented with a caliber reduction between the proximal and distal aortic arch of more than 40% (median reduction 71%, range 43%–79%) and with increased z-scores of the DAo. Vorticity in the DAo of patients with DAo dilatation (median: −24 s −1, range: −26 s −1 - −8 s −1 ) was significantly increased in magnitude compared to controls (median: 0 s −1, range: −2 – +2) ( p < 0.01). Vorticity in the DAo of patients without DAo dilatatation was not significantly increased compared to controls. DAo z-scores were associated with increased vorticity. Conclusions: The findings of signficiantly increased vorticity and its association with increased DAo z-scores can potentially explain vascular alterations in the DAo of HLHS patients. This study gives motivation for further investigations and may ultimately lead to future Norwood procedure modifications. Highlights : Dilatation in the descending aorta of HLHS patients is associated with increased vorticity. Vorticity in the dilated descending aorta of HLHS patients is significantly increased compared to controls. Increased vorticity ininin the descending aorta can potentially explain vascular alterations in HLHS patients.